Central vein stenosis in hemodialysis vascular access: clinical manifestations and contemporary management strategies - Echefu, Gift; Stowe, Ifeoluwa; Lukan, Abdulkareem; Sharma, Gaurav; Basu-Ray, Indranill; Guidry, London; Schellack, Jon; Kumbala, Damodar (Frontiers in Nephrology, 2023)
Central venous stenosis is a significant and frequently encountered problem in managing hemodialysis (HD) patients. Venous hypertension, often accompanied by severe symptoms, undermines the integrity of the hemodialysis access circuit. In central venous stenosis, dialysis through an arteriovenous fistula is usually inefficient, with high recirculation rates and prolonged bleeding after dialysis. Central vein stenosis is a known complication of indwelling intravascular and cardiac devices, such as peripherally inserted central catheters, long-term cuffed hemodialysis catheters, and pacemaker wires. Hence, preventing this challenging condition requires minimization of central venous catheter use. Endovascular interventions are the primary approach for treating central vein stenosis. Percutaneous angioplasty and stent placement may reestablish vascular function in cases of elastic and recurrent lesions. Currently, there is no consensus on the optimal treatment, as existing management approaches have a wide range of patency rates.